THE EFFECTIVENESS OF MICROFERTILIZERS FOR SEED TREATMENT AND FOLIAR APPLICATIONS OF WINTER WHEAT CROPS - Hanhur, V. V.; Kocherha А. А.; Pypko О. S.; Len, O. I. (Scientific Progress & Innovations, 2021)
Winter wheat (Triticum aestivum L.) is the main grain food crop of Ukraine, which is sown annually on the area of about 6.0–6.5 million hectares. It should be noted that in today's conditions an effective agrotechnological method of cultivation in increasing and stabilizing crop yields can be widespread use of biological fertilizers, plants growth regulators, stimulating substances and micro-fertilizers. The purpose of the study was to determine the effect of micro-fertilizers on the productivity and grain quality of winter wheat at pre-sowing seed treatment and foliar application. During the study the following scientific methods were used: analysis, synthesis, field scientific method, and statistical analysis of the experimental data. According to results of the study in the Left-Bank Forest-Steppe of Ukraine, it has been found that the number of productive stems per area unit in the variant of seed treatment with micro-fertilizers increased by 5.5–6.8 %, and in the variant with foliar application – by 7.1–12.2 %, as compared to the control. The plants’ spike length in the treated variants ranged from 6.8 to 7.4 cm, which is 2.1–14.9 % higher than in the control. The number of grains per spike varied from 26.0 to 37.1, or they were formed by 7.4–14.8% more than in the variants without micro-fertilizers’ applications. The maximum grain yield of winter wheat (5.62–5.63 t/ha-1) was obtained by combining of seed treatment with Vuxal Terios U (1.4 l/t) or Vuxal Terios M (1.5 l/t) microfertilizers and foliar fertilization with Vuxal Microplant (1.0 l/ha) in the phases of tillering, leaf tube forming, and the beginning of coming into ear. The positive effect of Vuxal micro-fertilizer application on grain quality indicators of Vdala winter wheat variety was clearly expressed. Thus, the pre-sowing seed treatment with microelements provided an increase in thousand-kernel weight by 0.8–1.0 g or 2.0–2.5 %, and in the variants with combination of pre-sowing seed treatment and foliar application at different winter wheat growing stages the grain weight increased by 1.8–3.3 g or 4.4–8.1 %. Gluten content in winter wheat grain in the variants with micro-fertilizers’ applications was by 3.4–8.8 % higher (absolute) as compared with the control. In terms of quality, the grain corresponded to the first class.